Social Movements, Social Media and Symbolic Resources - La Rosa, Amaro (2016)
The paper presents an updated approach of the social media role in the contemporary social movements. Drawing from the explanation of some viewpoints about interaction in the social media, a brief review about social movements theory and their implications is presented, emphasizing in their relationship with communication processes and specific storytellings.. Finally, some symbolic resources used by social movements in diverse realities are described.